COMPARATIVE ASSESSMENT OF THE PATHOLOGY OF DENTAL HARD TISSUES AND PERIODONTITIS IN PATIENTS WITH CHRONIC RENAL FAILURE WITH CHRONIC PYELONEPHRITIS AND GLOMERULONEPHRITIS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Nasal bone fractures represent one of the most prevalent types of facial trauma, accounting for approximately 40% of all facial injuries. These fractures occur across all age groups, from young children to adults, and result from various traumatic mechanisms. The etiology of nasal fractures includes direct impact during physical altercations, sports injuries, traffic accidents, falls, and even unusual causes such as mobile phone impact. Accurate diagnosis of nasal bone fractures presents significant challenges for clinicians, particularly in emergency settings. While conventional radiography in lateral projection remains widely used, it often leads to missed diagnoses due to subtle fracture lines and overlapping anatomical structures. Computed tomography (CT) has emerged as the gold standard diagnostic method, providing detailed visualization of fracture patterns, displacement of fragments, and associated injuries to adjacent facial structures including the maxilla, zygomatic bones, and orbital walls.